2020
DOI: 10.2147/rmhp.s270553
|View full text |Cite
|
Sign up to set email alerts
|

<p>A Country Pandemic Risk Exposure Measurement Model</p>

Abstract: The purpose of this study is to develop a Pandemic Risk Exposure Measurement (PREM) model to determine the factors that affect a country's prospective vulnerability to a pandemic risk exposure also considering the current COVID-19 pandemic. Methods: To develop the model, drew up an inventory of possible factor variables that might expose a country's vulnerability to a pandemic such as COVID-19. This model was based on the analysis of existing literature and consultations with some experts and associations. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 50 publications
1
36
0
Order By: Relevance
“…The aim of the study was to examine correlations between the change in new COVID-19 cases per million population and macroeconomic indicators, well-being indicators and healthcare systems' capacity in the first wave of the COVID-19 pandemic. Most recent studies have focused on demographic, socio-economic and health characteristics and the COVID-19 pandemic ( 2 , 6 , 7 , 17 ). In this study we were particularly interested in assessing whether countries' economic performance, as it is captured by GDP per capita, might be associated with COVID-19 spread in 38 European countries, in the early stages.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The aim of the study was to examine correlations between the change in new COVID-19 cases per million population and macroeconomic indicators, well-being indicators and healthcare systems' capacity in the first wave of the COVID-19 pandemic. Most recent studies have focused on demographic, socio-economic and health characteristics and the COVID-19 pandemic ( 2 , 6 , 7 , 17 ). In this study we were particularly interested in assessing whether countries' economic performance, as it is captured by GDP per capita, might be associated with COVID-19 spread in 38 European countries, in the early stages.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has to be recognized that these individual factors are likely to be influenced by various country specific parameters including lockdown policies ( 12 ), public expenditure in health ( 13 ) and other country-specific determinants such as level of sanitation ( 14 ), healthcare support i.e., number of acute care beds, hospital beds and number of physicians; ( 15 ), and social support ( 16 ). Grima et al ( 17 ) indicated that monitoring of demographic features, country's activity features, economic exposure and societal vulnerability could help a country strengthen its capacity to meet the economic, social and in turn healthcare demands due to pandemic hazards such as COVID-19.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The evidence is overwhelming that activation of innate immunity before and after the AIS and COVID-19 with adaptive immunity implications after the index events of AIS and COVID-19 share similar pathobiology and trajectory. These facts have already been documented so far in large populations of Eur-Asia with prominent public health consequences (54,55). Unlike its innate counterpart, the adaptive immunity is critically important for the attenuating inflammatory response during the recovery process both in the context of AIS and COVID-19 ( See the table one, with kind permission from Wijeratne et al, Frontiers in Neurology,2021, Under the creative common license (56).…”
Section: Nlr and Its Role In Predisposition To Acute Ischemic Strokementioning
confidence: 95%
“…Surprisingly, although we live in an era of rapidly escalating competition among leading powerhouses, there was an unprecedented degree of unity in the global response to Coronavirus spreading. Unlike any previous time in the modern era, these interventions included border shut-down and stringent control of the flow of passengers across land, sea and flight routes among countries [ 14 ]. Even more, in the case of large or most heavily affected nations such as China, Iran, Italy, Spain, the U.S., strict control of passenger flows within single nations among large cities and regions was also assumed.…”
Section: Corona-triggered Global Macroeconomic Crisis Of the Earlymentioning
confidence: 99%